DEVELOPMENT OF CORPORATE SOCIAL RESPONSIBILITY (CSR) MODEL OF PRODUCTIVE INDEPENDENT BUSINESS ESTABLISHMENT OF MARINE RESOURCES MANAGEMENT (CASE STUDY OF PT. INDONESIA POWER UP SEMARANG) (International Conference of Graduate School on Sustainability (ICGSS), 2018)
Investors or companies in Indonesia have an obligation to perform Corporate Social Responsibility (CSR) activities by allocating part of the funds taken from company profits. PT. Indonesia Power UP Semarang, located in Tanjung Mas Port area, which administratively  located in North Semarang Subdistrict, has a high commitment to perform these activities. Aside from complying the government's recommendation, another underlying factor is to support the Government of Semarang to reduce poverty, especially in the North Semarang Subdistrict which is the first ring of Corporate Social Responsibility goal of PT. Indonesia Power UP Semarang. This commitment is stated in the Indonesia Power In Power Care Program, a Corporate Social Responsibility (CSR) program which designed through the identification of problems and mapping the needs of the target community. The performed program is empowering and sustainable. This program targets community groups with a fisherman profession to be more creative in managing marine resources. The activities are exercised in the form of providing capital assistance, equipment, marketing management training, packaging management training, and production quality improvement training.